Unleashing Adult Learners’ Numeracy Agency Through Self-Determined Online Professional Development - Walsh, Chris; Bragg, Leicha; Muir, Tracey; Oates, Greg (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Opportunities for self-determined online professional development (OPD) are emerging, but their potential for increasing adult learners’ agency is not yet fully realised. Faced with the problem of successfully designing a self-determined comprehensive evidence-based online numeracy resource for educators who are often time poor and do not engage with online learning unless they are intrinsically motivated, we engaged in design research to conceptualise the Birth to Level 10 Numeracy Guide for educators and families. The Birth to Level 10 Numeracy Guide fosters educators’ and adult learners’ numeracy capability across numeracy focus areas from birth to level 10 (16-year-olds). This extensive OPD resource incorporates consistent design elements, double-looped learning, nonlinear learning, self-reflection, and metacognition activities to foster educators’ pedagogical content knowledge (PCK) through experiential learning. With a section dedicated to families, the resource provides suggestions and advice to parents and carers on everyday, authentic activities to develop children and young people’s numeracy understandings at home and in the local community. As education systems continue to grapple with the disruption brought about by the COVID-19 pandemic, the Birth to Level 10 Numeracy Guide is a timely, freely accessed, viable, and scalable option for providing low-cost OPD.